When distance is not an obstacle. Several preliminary considerations on Liberalitas coin types of Nikopolis ad Istrum and Marcianopolis (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
The present study highlights a noteworthy and atypical reverse type within Roman Provincial Coinage of Moesia Inferior, but also in general. It features Liberalitas standing and holding a counting table and cornucopia, a depiction commonly associated with imperial coinage. Surprisingly, Nikopolis ad Istrum issued coins with this image during a very specific period, the tenure of Statius Longinus under the brief rule of Macrinus and Diadumenianus (April-June/August AD 217). Still, not only Nikopolis, but also Marcianopolis produced coins with this depiction, doing so during the afore-mentioned reign (under the governor Pontianus, June/August – November/December AD 217) and the period of Elagabalus (AD 218-222). Given the exceptional character of these coin types in the case of the so-called “Greek Imperials”, this research seeks to explore a possible context for their emergence in the cities under consideration based on the currently available data (literary, epigraphic and numismatic) and to contour several preliminary observations.